Laser scanning microscopy of HTS films and devices (Review Article) - Zhuravel, A.P.; Sivakov, A.G.; Turutanov, O.G.; Omelyanchouk, A.N.; Anlage, S.M.; Lukashenko, A.; Ustinov, A.V.; Abraimov, D. (Физика низких температур, 2006)
The work describes the capabilities of laser scanning microscopy (LSM) as a spatially-resolved
method of testing high–Tc materials and devices. The earlier results obtained by the authors are
briefly reviewed. Some novel applications of the LSM are illustrated, including imaging the HTS
responses in rf mode, probing the superconducting properties of HTS single crystals, development
of two-beam laser scanning microscopy. The existence of the phase slip lines mechanism of
resistivity in HTS materials is proven by LSM imaging.